TATA KELOLA PENDIDIKAN PESANTREN DALAM MEMBANGUN KARAKTER SANTRI DI ERA DISRUPSI - Mardia (Department of Islamic Education Management, 2024)
This article discusses Islamic boarding school governance in building the character of students in the era of disruption. Islamic boarding school is one of the Islamic boarding school institutions that will produce generations of Indonesians to become great 'ulama', Muslim scholars and also a generation that has national character and good morals. This article focuses on studying how Islamic boarding schools respond to global developments. Islamic boarding schools are an ideal educational system in nurturing national character, because in Islamic boarding schools students will be trained to have moral ethics, rituals, religious ceremonies, arts and national culture. In the current era of information technology development, learning approaches have experienced very rapid development so that they can change people's thinking patterns. The availability of information technology connected to the internet makes it easy for everyone to access knowledge. So, Islamic boarding schools must also be able to actualize these developments, namely by developing Islamic boarding school curricula that are in line with the needs of the times.